2017
DOI: 10.1590/1516-4446-2016-2141
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to early identification of autism in Brazil

Abstract: Objective: Parents of children with autism spectrum disorders (ASD) seem to perceive that their child's development is not following the normal pattern as early as the first year of life. However, ASD children may not receive a diagnosis until they are of preschool age, especially in low-and middleincome countries. The objective of this study was to evaluate the pathway between initial parental concerns about atypical child development and ASD diagnosis in Brazil. Methods: Nineteen mothers whose children had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 14 publications
5
41
0
13
Order By: Relevance
“…Factors associated with age at ASD diagnosis. Of the 56 studies, 10 did not report any influencing factors on age at diagnosis (Cawthorpe, 2018;Garrido et al, 2018;Hausman-Kedem et al, 2018;Lo et al, 2017;Martinez et al, 2018;Masri et al, 2013;May et al, 2017;Mpaka et al, 2016;Nadeem et al, 2019;Ribeiro et al, 2017). However, 46 studies reported many possible influencing factors on age at ASD diagnosis, including type of ASD diagnosis, additional diagnoses and gender among the most frequently reported (Supplemental Material 2).…”
Section: Additional Analysesmentioning
confidence: 99%
“…Factors associated with age at ASD diagnosis. Of the 56 studies, 10 did not report any influencing factors on age at diagnosis (Cawthorpe, 2018;Garrido et al, 2018;Hausman-Kedem et al, 2018;Lo et al, 2017;Martinez et al, 2018;Masri et al, 2013;May et al, 2017;Mpaka et al, 2016;Nadeem et al, 2019;Ribeiro et al, 2017). However, 46 studies reported many possible influencing factors on age at ASD diagnosis, including type of ASD diagnosis, additional diagnoses and gender among the most frequently reported (Supplemental Material 2).…”
Section: Additional Analysesmentioning
confidence: 99%
“…Because of various barriers, children with ASD often do not receive a confirmatory diagnosis until preschool age, especially in LMICs. In a Brazilian survey, Ribeiro et al 67 found that most mothers sought help within 3 months of first suspicion and mentioned their concerns to pediatricians, but only one-third of such children were referred for further evaluation of ASD. The authors reported that in many instances, mothers were told by their pediatricians that "children should not be compared to each other" and that "boys have a slower development rate or are more agitated than girls."…”
Section: Figurementioning
confidence: 99%
“…The questions related to the environment had the least positive answers. These data reflect the families' concern in the financial resources to guarantee the child's access to health care, education, and leisure services; which can further intensify parental stress (10)(11)(12)(13)(14)(15) .…”
Section: Discussionmentioning
confidence: 77%